2019
DOI: 10.1016/j.gaitpost.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic foot muscle size can be measured reliably in weight bearing using ultrasound imaging

Abstract: Background:The intrinsic foot muscles (IFMs) are important contributors to optimal foot function. While assessment of IFM morphology using ultrasound imaging in non-weight bearing has been established, this does not evaluate the foot in its primary functional position of weight bearing.Research Question: Is ultrasound imaging a reliable and clinically feasible method of measuring IFM morphology in weight bearing, do these measures differ to those from nonweight bearing and are they associated with participant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
4
6
1
Order By: Relevance
“…As far as we know, this is the first study to report a reliable method for measuring the TP CSA using US. Our ICC scores were similar to or higher than those reported for other lower extremity muscles, which ranged from 0.57 to 0.99 15,26,29,30,34–36 . The SEM and LoA were also comparable to or lower than those seen in other studies 26,29,30 .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…As far as we know, this is the first study to report a reliable method for measuring the TP CSA using US. Our ICC scores were similar to or higher than those reported for other lower extremity muscles, which ranged from 0.57 to 0.99 15,26,29,30,34–36 . The SEM and LoA were also comparable to or lower than those seen in other studies 26,29,30 .…”
Section: Discussionsupporting
confidence: 86%
“…Our ICC scores were similar to or higher than those reported for other lower extremity muscles, which ranged from 0.57 to 0.99 15,26,29,30,34–36 . The SEM and LoA were also comparable to or lower than those seen in other studies 26,29,30 . For thickness measurements, our LoA ranged from 5.8% to 9.7%, whereas other researchers saw a range of 9% to 18% for foot and leg muscles 26,29 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In regard to foot disorders, such as pes pannus, Angin et al reported an increase in the thickness of the plantar fascia in patients with this foot condition, with overpronation being an associated risk factor for PF or Achilles tendinopathy pathologies [ 19 ]. Several authors support the use of USI for the assessment of the IFMs, considering its quick examination procedure, relatively cheap cost and portable features, which make it a suitable tool for clinicians and physical therapy researchers [ 20 ]. Recently, there has been exponential growth in the use of USI for the analysis of muscle quality due to its applicability.…”
Section: Introductionmentioning
confidence: 99%